2016
DOI: 10.4103/0022-3859.180553
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of fecal occult blood test in the acute hospital setting and its impact on clinical management and outcomes

Abstract: Background:Despite lack of evidence supporting the use of fecal occult blood test (FOBT) in the acute hospital setting, FOBT is commonly used in the inpatient setting for reasons other than colorectal cancer (CRC) screening.Aims:To evaluate practice trends in utilizing FOBT on inpatients and its impact on affecting clinical management and outcomes.Materials and Methods:A cross-sectional study of consecutive adult patients undergoing FOBT from January 1, 2011 to December 31, 2011 during an acute medical admissi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 10 publications
1
8
0
Order By: Relevance
“…A total of 3 colon cancer were found in the inappropriate group, although it is important to consider none of the FOBT testing was performed for this reason specifically. The study done by Mosadeghi et al [19] showed that the odds of getting further investigations are much higher when the results of the FOBT done for any reason is positive. Taking this finding and using it with our results, it is highly probable that if inappropriate FOBTs were not done for our patients, we would have had a smaller number of positive FOBT results leading to a fewer amounts of performed colonoscopies potentially leading to lower hospitalization cost and length of stay.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 3 colon cancer were found in the inappropriate group, although it is important to consider none of the FOBT testing was performed for this reason specifically. The study done by Mosadeghi et al [19] showed that the odds of getting further investigations are much higher when the results of the FOBT done for any reason is positive. Taking this finding and using it with our results, it is highly probable that if inappropriate FOBTs were not done for our patients, we would have had a smaller number of positive FOBT results leading to a fewer amounts of performed colonoscopies potentially leading to lower hospitalization cost and length of stay.…”
Section: Discussionmentioning
confidence: 99%
“…FIT was not intended as a replacement, but as it remained an orderable test for colorectal cancer screening, it appeared to have taken the place of gFOBT by some clinicians. Previous studies had sounded the alarm on the inappropriate use of FOBT in the acute hospital setting; [7][8][9][10][11][12][13][14][15][16][17] our study adds to this body of literature as the first study to exclusively evaluate FIT in this context. Our primary finding was that similar to gFOBT, the inappropriate use of FIT in the inpatient and emergency settings was widespread: of the 550 tests done, 99.5% of tests were done for indications other than colorectal cancer screening.…”
Section: Discussionmentioning
confidence: 92%
“…[7][8][9][10][11][12][13][14][15][16][17] Studies of FOBT (FIT or gFOBT) use for indications other than colorectal cancer screening have consistently shown that the tests are nearly always used inappropriately-often in the presence of confounding factors (such as certain medications for gFOBT) or contraindications, such as advanced age. [7][8][9][10][11][12][13][14][15][16][17] Such inappropriate use has led to high rates of both false-positive and false-negative results, with consequences such as delays in appropriate care (eg, colonoscopy for potential colorectal cancer or bleeding sources in the case of false-negative results) or unnecessary procedures and consultations from false-positive results and has little impact on clinical decision-making for hospitalized patients. [7][8][9][10][12][13][14][15][16][17] In this setting, it leads to added cost and has potential for inaccurate results without providing clinical value.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies on the utility of inpatient gFOBT have found that the initial rationale for testing are also indications for endoscopy and FOBT results should not determine the need for endoscopy [ 2 - 5 , 7 ]. Uninvestigated iron deficiency anemia (IDA) and overt GI bleeding are both appropriate indications for endoscopy and are two of the most common reasons for obtaining a gFOBT in most audit studies.…”
Section: Discussionmentioning
confidence: 99%